Effectiveness Network Governance In Making of Special Regional Regulations In Papua Province - Bonso, Hamjah; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2018)
Abstract-Since the implementation of Special Autonomy law, the system of governance of Papua province experiencing changes in terms namely institutional establishment of the Papuan People's Assembly (MRP). The presence of MRP institutions greatly affect the implementation of the Provincial Government of Papua, especially in the manufacture of specific local regulations. The purpose of this study was to determine the effectiveness of the network between local governance institutions in the manufacture of specific local regulations (Perdasus) in Papua province. This study uses